Interaction of Heavy Metal Ions with Carbon and Iron Based Particles - Fialova, Dana; Kremplova, Monika; Melichar, Lukas; Kopel, Pavel; Hynek, David; Adam, Vojtech; Kizek, Rene (Materials (Basel, Switzerland), 2014)
Due to the rapid development of industry and associated production of toxic waste, especially heavy metals, there is a great interest in creating and upgrading new sorption materials to remove these pollutants from the environment. This study aims to determine the effectiveness of different carbon forms (graphene, expanded carbon, multi-wall nanotubes) and paramagnetic particles (Fe₂O₃) for adsorption of cadmium(II), lead(II), and copper(II) on its surface, with different interaction time from 1 min to 24 h. The main attention is paid to the detection of these metals using differential pulse voltammetry. Based on the obtained results, graphene and Fe₂O₃ are found to be good candidates for removal of heavy metals from the environment.
Keywords: electrochemical detection; voltammetry; multi-wall nanotubes; expanded carbon; heavy metal ions; paramagnetic particle; graphene